Endovascular technologies and reconstructive interventions on profound femoral artery at revascularization of multilevel stenotic-occlusive process of infrainguinal arterial channel - Herasymiuk, Nazar I.; Husak, Mykhailo O.; Venher, Ihor K.; Kovalskyy, Dmytro V.; Loyko, Ihor I.; Selskyy, Boryslav P. (Journal of Education, Health and Sport, 2020)
Introduction. Number of patients with obliterating lesions of the aorta and main arteries of the lower extermities has been steadily increasing every year. When choosing the scope of surgical treatment all the features of the multilevel stenotic-occlusive process of the infrainguinal arterial bed should be taken into account. Purpose. To improve the results of revascularization of the infrainguinal arterial bed by applying surgical intervention on profound femoral artery and endovascular methods to restore permeability of the outflow arteries. Materials and methods. The work is based on the results of examination and surgical treatment of 264 patients with stenotic-occlusive process of the infrainguinal arterial bed. There were four groups of patients. The basis of revascularization interventions on the infranguinal artery was shunt surgery. Bypass surgery was performed using a reverse autovein. The combined shunt was used for localization of the distal anastomosis at the level of the popliteal, shin arteries, tibioperinel trunk. Results. In atherosclerotic stenotic-occlusive lesions of the infrainguinal arterial bed of the lower extremity, the volume of surgical treatment depends on the level of the occlusive process, the functional state of the PFA and the blood flow pathways. And the method of surgical intervention in shunt interventions is determined by the type of distal lesion and the level of imposition of distal and proximal anastomoses. Conclusion. The use of endovascular methods of revascularization and reconstructive interventions on PFA in combination with femoral-distal shunt operations contributes to good and satisfactory results of surgical treatment of stenotic-occlusive processes of the infrainguinal arterial bed.